Study on the Spatial Coordinated Development of Guanzhong-Tianshui Economic Region from the Perspective of New Regionalism - Zhang, You; Qin, Hua (International Journal of Global Economics and Management, 2024)
Guanzhong -Tianshui Economic Region, being one of the national economic development zones along the “Belt and Road”, holds a crucial geographical position and possesses substantial economic strategic value. Drawing upon the connotation and viewpoint of “new regionalism”, this paper analyzes the current situation and contradictions in the spatial development of the Guan-Tian economic region, and explores its mechanism for spatial coordinated development. In the future spatial development of the Guan-Tian economic region, it is essential to eliminate administrative barriers and establish regional coordination mechanisms. Furthermore, attention should be given to constructing a public participation mechanism in the planning process, promoting the building and sharing of infrastructure to enhance multi-field connectivity, balancing regional development goals, and diversifying regional coordination mechanisms.